2023
DOI: 10.5217/ir.2021.00168
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in fecal microbiota associated with clinical phenotypes and prognosis in Korean patients with inflammatory bowel disease

Abstract: Background/Aims: The fecal microbiota of Korean patients with inflammatory bowel disease (IBD) was investigated with respect to disease phenotypes and taxonomic biomarkers for diagnosis and prognosis of IBD.Methods: Fecal samples from 70 ulcerative colitis (UC) patients, 39 Crohn’s disease (CD) patients, and 100 healthy control individuals (HC) were collected. The fecal samples were amplified via polymerase chain reaction and sequenced using Illumina MiSeq. The relationships between fecal bacteria and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Microbial arginine and isoprene pathways were at higher relative abundance in the gut microbiome of CD patients (Hu et al 2021 ). Recent analysis of the faecal microbiota of Korean patients with IBD (70 with UC, 39 with CD) and 100 healthy control individuals using Illumina MiSeq revealed that R. gnavus was a biomarker for prognosis in CD (Shin et al 2022 ). Whole genome sequencing of R. gnavus isolates coupled with metagenomic analyses from 20 IBD patients and 12 controls revealed two phylogenetically distinct R. gnavus strains that appeared differentially enriched in IBD (Hall et al 2017 ), highlighting the importance of analysing the effect of R. gnavus on IBD at the strain level.…”
Section: Association Between R Gnavus and Diseasesmentioning
confidence: 99%
“…Microbial arginine and isoprene pathways were at higher relative abundance in the gut microbiome of CD patients (Hu et al 2021 ). Recent analysis of the faecal microbiota of Korean patients with IBD (70 with UC, 39 with CD) and 100 healthy control individuals using Illumina MiSeq revealed that R. gnavus was a biomarker for prognosis in CD (Shin et al 2022 ). Whole genome sequencing of R. gnavus isolates coupled with metagenomic analyses from 20 IBD patients and 12 controls revealed two phylogenetically distinct R. gnavus strains that appeared differentially enriched in IBD (Hall et al 2017 ), highlighting the importance of analysing the effect of R. gnavus on IBD at the strain level.…”
Section: Association Between R Gnavus and Diseasesmentioning
confidence: 99%
“…[30,31] Additionally, certain Lactobacillus species are proposed to be linked with extensive disease involvement and heightened disease activity. [32] Although no clear evidence supports the association of a speci c type of gut bacteria with UC development, these ndings suggest that as the disease progresses, the gut environment may change to favor the colonization and expression of certain bacteria. Thus, the changing gut environment should be considered with the progression of the disease through further research.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have consistently reported a decrease in microbial diversity in IBD patients compared with HC [20][21][22]. Several studies have observed signi cant differences in the gut microbiome of patients with IBD compared with HC [23][24][25][26]. When the relative abundance was compared at the phylum level, both Firmicutes and Bacteroidetes decreased in IBD compared with HC, whereas Actinobacteria and Proteobacteria increased signi cantly [27,28].…”
Section: Discussionmentioning
confidence: 99%